Postcard from Richard Willstätter to Georg Bredig, October 1925 (1925)
Richard Willstätter (1872-1942), a German organic chemist, inventor of paper chromatography, and 1915 Nobel Prize winner, thanks Georg and Rosa Bredig for an invitation.
Keywords: Bredig, Georg, 1868-1944; Willstätter, Richard, 1872-1942; Nobel Prize winners